Cytokine gene polymorphisms in preterm infants with necrotising enterocolitis: genetic association study. Issue 2 (3rd September 2007) - Henderson, G; Craig, S; Baier, R J; Helps, N; Brocklehurst, P; McGuire, W
Abstract : Background: The inflammatory cytokine cascade is implicated in the pathogenesis of necrotising enterocolitis (NEC). Genetic association studies of cytokine polymorphisms may help to detect molecular mechanisms that are causally related to the disease process. Aim: To examine associations between the common genetic variants in candidate inflammatory cytokine genes and NEC in preterm infants. Methods: Multi-centre case–control and genetic association study. DNA samples were collected from 50 preterm infants with NEC and 50 controls matched for gestational age and ethnic group recruited to a multi-centre case–control study. Ten candidate single-nucleotide polymorphisms in cytokines previously associated with infectious or inflammatory diseases were genotyped. The findings were included in random-effects meta-analyses with data from previous genetic association studies. Results: All allele distributions were in Hardy–Weinberg equilibrium. None of the studied cytokine polymorphisms was significantly associated with NEC. Four previous genetic association studies of cytokine polymorphisms and NEC in preterm infants were found. Meta-analyses were possible for several single-nucleotide polymorphisms. These increased the precision of the estimates of effect size but did not reveal any significant associations. Conclusions: The available data are not consistent with more than modest associations between these candidate cytokine variant alleles and NEC in preterm infants. Data from future association studies of these polymorphisms may be added to the meta-analyses to obtain more precise estimates of effects sizes.